Little flowers of St. Francis of Assisi - Francis, Saint; Arnold, T. W.; Biagi, Guido (New York Chacco & Windus, 1908)
St. Francis of Assisi's ecstatic embrace of a life of poverty revolutionized Christianity even as it transformed the ethics of the West. In this luminous and lively book, St. Francis's followers preserved his legend and those of his first disciples, combining stories of miracles with convincing portraits of men who were no less human for having been touched by God.
Keywords: Francis, of Assisi, Saint -- 1182-1226; Christian saints; Franciscanen